Utility of Cytological Grading in Proliferative Epithelial Lesions of Breast - Gali, Sai Chandana; M, Udaya Kumar; J, Nirmala M; R, Prashanth; S, Ramaswamy A (Annals of Pathology and Laboratory Medicine, 2019)
Background: Breast carcinoma is the second most common malignancy in women. Fine needle aspiration cytology of breast is rapid, reliable and safe diagnostic tool to distinguish between neoplastic and non neoplastic lesions. Cytological grading of the smears can provide valuable prognostic information. AIMS AND OBJECTIVES: To study the utility of Masood cytological grading system and to compare it against a new proposed cytological grading system in proliferative epithelial lesions of breast. Methods: The Papanicolaou (PAP) stained Fine Needle Aspiration Cytology (FNAC) smears of proliferative breast lesions were cytologically graded by the Masood cytological grading system and by the newly proposed grading system by two observers independently. Results were correlated with the histopathological diagnosis. Result: In the study period of 2 years, 54 proliferative epithelial lesions were studied of which 47 were proliferative breast disease without atypia and seven proliferative breast diseases with atypia. 42/54 cases in newly proposed system showed concordance with existing Masood grading system. p-value is 0.000 (< 0.005) which is significant. Sensitivity, specificity, positive predictive value and negative predictive value for newly proposed grading system were 88.67%, 100%, 100% and 85.71% respectively. Conclusion: A simple slide based scoring system of epithelial lesions of breast is a useful tool in the prognostication and prediction of behavior of proliferative epithelial lesions.